2013
DOI: 10.1017/s143192761201433x
|View full text |Cite
|
Sign up to set email alerts
|

In VitroCharacterization of Multipotent Mesenchymal Stromal Cells Isolated from Palatal Subepithelial Tissue Grafts

Abstract: The aim of this study was to analyze whether the mesenchymal stromal cells (MSCs) isolated from palatal tissue grafts harvested in order to cover gingival recessions have the basic characteristics of stem cells. The palatal tissue cells were processed using a special culture medium that stimulated the development of only undifferentiated cellular lines. Cells at passage 4 were evaluated by flow cytometry to examine the expression of specific surface markers and were tested for multilineage differentiation capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 65 publications
2
40
0
Order By: Relevance
“…Stem cells have also been isolated from new, more accessible sources, including gingiva [Yang et al, 2013], oral mucosa, palatal connective tissue [Roman et al, 2013], and palatal periosteum [Caballero et al, 2010]. The main goal of the present study was to characterize and compare a novel stem cell population obtained from PAT-and LAT-derived stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Stem cells have also been isolated from new, more accessible sources, including gingiva [Yang et al, 2013], oral mucosa, palatal connective tissue [Roman et al, 2013], and palatal periosteum [Caballero et al, 2010]. The main goal of the present study was to characterize and compare a novel stem cell population obtained from PAT-and LAT-derived stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Its capability for rapid regeneration may be explained by the potential presence of at least one stem cell type within the tissue or by the existence of growth factors, such as basic fibroblast growth factor, in saliva [Grimm et al, 2014]. Previous research suggested that PAT provided an accessible source of MSCs, which could be used for tissue engineering and tissue regeneration of extraoral tissues in periodontal disease [Roman et al, 2013]. Research also showed that stem cells derived from palatal tissue could be of enormous benefit in regenerative processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations